ANALISIS CARA PENANGANAN DENGAN KEJADIAN INFEKSI SALURAN KEMIH PADA PASIEN DI POLIKLINIK UROLOGI RSUD DR M YUNUS BENGKULU - Liza Fitri Lina; Ferasinta Ferasinta; Eva Oktavidiati; Dwi Puji Lestari (LPPM STIKES Muhammadiyah Kendal, 2019)
Urinary tract infection is a pathological condition that has been very long known and can be found in various primary health care to subspesialistik. The purpose of this study is to analyze the handling aspect with urinary tract infections in patients in urology clinic RSUD Dr.. M Yunus Bengkulu. The research design used was qualitative with descriptive approach. Informant research method in this research using technique